The steps to war : an empirical study - Senese, Paul Domenic; Vasquez, John A., 1945- (Princeton University Press, 2008)
The question of what causes war has concerned statesmen since the time of Thucydides. The Steps to War utilizes new data on militarized interstate disputes from 1816 to 2001 to identify the factors that increase the probability that a crisis will escalate to war. In this book, Paul Senese and John Vasquez test one of the major behavioral explanations of war--the steps to war--by identifying the various factors that put two states at risk for war. Focusing on the era of classic international politics from 1816 to 1945, the Cold War, and the post-Cold War period, they look at the roles of terri.